2015
DOI: 10.33145/2304-8336-2015-20-283-310
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression, telomere and cognitive deficit analysis as a function of Chornobyl radiation dose and age: from in utero to adulthood

Abstract: Мета дослідження-вивчити можливі ефекти малих доз іонізуючого випромінювання на когнітивні функції до рослих і опромінених внутрішньоутробно. Матеріали і методи. Проведено дослідження когнітивних тестів, довжини теломер і експресії генів, що регу люють функцію теломер в учасників ліквідації наслідків аварії на Чорнобильській АЕС (УЛНА), опромінених у дозі менше 500 мЗв (n = 326) та осіб, опромінених внутрішньоутробно в перші дні після аварії у м. При'пяті (n = 104). Нейрокогнітивна оцінка включала основні когн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A statistically significant dose-dependent increase in the level of mental disorders (as assessed by the Brief Psychiatric Rating Scale (BPRS) [ 74 ]) was found among 326 Ukrainian cleanup workers exposed to dose under 500 mSv [ 69 ]. Higher risks of organic psychoses and non-psychotic organic brain damages were found among 198 Ukrainian Chernobyl liquidators who intervened in 1986–1987, relative to 42 internal controls exposed to doses < 50 mSv (RR = 3.15; 95% CI: 2.60, 3.70 and RR = 1.99; 95% CI: 1.60, 2.50, respectively) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…A statistically significant dose-dependent increase in the level of mental disorders (as assessed by the Brief Psychiatric Rating Scale (BPRS) [ 74 ]) was found among 326 Ukrainian cleanup workers exposed to dose under 500 mSv [ 69 ]. Higher risks of organic psychoses and non-psychotic organic brain damages were found among 198 Ukrainian Chernobyl liquidators who intervened in 1986–1987, relative to 42 internal controls exposed to doses < 50 mSv (RR = 3.15; 95% CI: 2.60, 3.70 and RR = 1.99; 95% CI: 1.60, 2.50, respectively) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies observed no significant difference in verbal memory between clean-up workers exposed to greater than 0.5 Sv and clean-up workers exposed to less than 0.02 Sv, but observed reduced brief global cognitive scores in the former group (Bazyka et al 2015). Such studies (Loganovsky et al 2015;Bazyka et al 2015) should be treated cautiously if interpreting any effect to radiation dose, due to limited control for other variables. Indeed, Bazyka et al (2015) observed higher rates of stress-related disorders in the most exposed clean-up workers, therefore any observed association between dose and cognitive function could be attributed to psychological stress rather than to radiation itself.…”
Section: Observations From Human Studiesmentioning
confidence: 93%
“…Furthermore, in a cohort working on the Chernobyl 'Shelter Object' project (0-0.0567 Sv total dose from external and internal sources), an increase in verbal memory deficits were observed compared to before the project (Loganovsky et al 2015). Other studies observed no significant difference in verbal memory between clean-up workers exposed to greater than 0.5 Sv and clean-up workers exposed to less than 0.02 Sv, but observed reduced brief global cognitive scores in the former group (Bazyka et al 2015). Such studies (Loganovsky et al 2015;Bazyka et al 2015) should be treated cautiously if interpreting any effect to radiation dose, due to limited control for other variables.…”
Section: Observations From Human Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, in 326 Ukrainian Chernobyl cleanup workers, those with doses above 100 mSv had a higher prevalence of cognitive deficits compared with groups with lower or no exposure. The most severe deficits were seen in those with doses above 500 mGy ( Bazyka et al, 2015 ). Follow-up studies of the Ukrainian Chernobyl cleanup workers also suggest a dose-dependent increase in cognitive impairment from radiation exposure ( Loganovsky et al, 2018 , 2020 ).…”
Section: Evidence Base Describing the Impact Of Ionizing Radiation On...mentioning
confidence: 99%